The Influence of Good Corporate Governance and Asset Management on Financial Performance with ERP (Enterprise Resource Planning) as a Mediating Variable in the Construction Subsector in Indonesia in 2023 - Ismi Rahmawati, Yustina; Herawati, Aty (Journal of Accounting and Finance Management, 2025)
The aim of this research is to determine the influence of good corporate governance and asset management on financial performance with ERP (enterprise resource planning) as mediation variable in construction subsector in Indonesia in 2023. The object of this research is all company in construction subsector in Indonesia. The objectives are, (1) To determine the influence of Good Corporate Governance (GCG) on Enterprise Resource Planning (ERP), (2) To determine the influence of Asset Management on Enterprise Resource Planning (ERP), (3) To determine the effect of Enterprise Resource Planning (ERP) on Financial Performance. (4) To determine the influence of Good Corporate Governance (GCG) on financial performance both directly and indirectly through ERP as a mediating variable, and (5) To determine the influence of Asset Management on financial performance both directly and indirectly through ERP as a mediating variable. The methodology used in this research is descriptive statistical analysis, path analysis, and chi square analysis. And result of this research is Good Corporate Governance (GCG) has a significant influence on Enterprise Resource Planning (ERP) with a direct influence of 73.2%. ERP itself has a significant influence on Financial Performance, with a value of 1.570 and a significance of 0.043, and a direct influence of 246%. Meanwhile, GCG does not have a direct influence on Financial Performance, but through ERP as a mediating variable with an indirect influence of 134%. This shows that ERP fully mediates the relationship between GCG and Financial Performance.